Analisis Semiotika Pesan Moral Film Dua Garis Biru karya Gina S. Noer - Nadira Hajarani; Rifa Aisa Nabillah; Sella Noviyah Ramadhani; Weni Adityasning Arindawati (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
The film “Dua Garis Biru” is a romantic drama film by Ginatri S. Noer which will be shown in Indonesian cinemas in 2019. It tells of a pair of high school student lovers who have free sex and end in pregnancies outside of marriage, to the importance of the role of parents and the environment in growing up. child flower. This film can open our eyes about the importance of sexual education from an early age, psychology of adolescents & communication between family members. This study uses a qualitative study with technical content analysis. This study will analyze the moral message about early marriage in "Dua Garis Biru" where, the contents of the message contained in this film will be observed, both verbal and nonverbal moral messages. This research uses qualitative descriptive research with research methods that use Charles Sanders Pierce's semiotic analysis with a constructivist paradigm. This method is used in order to help the public to see and interpret the signs of a film, that from the film "Dua Garis Biru" it can be seen what moral messages are obtained through the signs. Keywords: Film, Semiotics, Moral Message, Constructive Paradigm.